Inovasi Pembelajaran IPA: Lembar Kegiatan Mahasiswa Berbasis Studi Kasus untuk Meningkatkan Kosakata Ilmiah Mahasiswa - Septiani, Devi; Djufri, Elyas; Lestari, Titi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The development of vocabulary across various fields of science, including science education, continues to increase. However, the emergence of new terms that resemble commonly known words often leads to misunderstandings in comprehending the material. This study aims to develop a Student Worksheet (LKM) designed to enhance mastery of scientific vocabulary in science education. The research employed a development study using the 4D model (define, design, develop, and disseminate), with data analyzed both quantitatively and qualitatively. The instruments used included product evaluation sheets from experts and student response sheets. The developed product is a worksheet containing unique news about nature, along with activities to check a list of unique events and their scientific names in English. The validation results from experts showed an average score of 3.51, categorized as excellent, while the practicality assessment by students resulted in a score of 3.54, also falling under the excellent category.